The ditson trio album for violin, cello and pianoI Violoncello - SUDESSI, P [et.al] (Oliver Ditson co., 1922)
A Petits PasnAngel's dreamnDancers, thenElegynEntr'acte II from RosamondenFairy TalenForgottennFuniculi-FuniculanLa PoupeenMemoriesnMinuet in Gn'O Sole MionSolitary Wandere